Targeted expression of shibire[ts] and semaphorin 1a reveals critical periods for synapse formation in the giant fiber of Drosophila. - Murphey, R.K.; Froggett, S.J.; Caruccio, P.; Shan-Crofts, X.; Kitamoto, T.; Godenschwege, T.A. (Development, 2003)
In order to determine the timing of events during the assembly of a neural circuit in Drosophila we targeted expression of the temperature-sensitive shibire gene to the giant fiber system and then disrupted endocytosis at various times during development. The giant fiber retracted its axon or incipient synapses when endocytosis was blocked at critical times, and we perceived four phases to giant fiber development: an early pathfinding phase, an intermediate phase of synaptogenesis, a late stabilization process and, finally, a mature synapse. By co-expressing shibire(ts) and semaphorin 1a we provided evidence that Semaphorin 1a was one of the proteins being regulated by endocytosis and its removal was a necessary part of the program for synaptogenesis. Temporal control of targeted expression of the semaphorin 1a gene showed that acute excess Semaphorin 1a had a permanent disruptive effect on synapse formation.